Antibody-drug conjugates as immuno-oncology agents in colorectal cancer: targets, payloads, and therapeutic synergies - Wang, Yihan; Lu, Kai; Xu, Yang; Xu, Shengshan; Chu, Hongyu; Fang, Xuedong (Frontiers in Immunology, 2025)
Colorectal cancer (CRC), particularly the immunologically “cold” microsatellite-stable (MSS) subtype, remains profoundly resistant to immune checkpoint inhibitors. Antibody-drug conjugates (ADCs) are rapidly emerging as a transformative therapeutic modality poised to overcome this challenge. This review reframes ADCs beyond their role as targeted cytotoxics, repositioning them as sophisticated immuno-oncology agents. The central thesis is that by strategically selecting payloads such as topoisomerase inhibitors or auristatins, modern ADCs can induce immunogenic cell death (ICD) or pyroptosis. This mechanism effectively functions as an in situ vaccine, transforming the tumor microenvironment from “cold” to “hot” by promoting dendritic cell activation and T-cell infiltration. We provide a comprehensive overview of the ADC landscape, examining key targets on bulk tumor cells (CEACAM5, HER2), cancer stem cells (LGR5, GPR56), and stromal components. We conclude that the future of ADCs in CRC lies in their rational application as immune-priming agents, creating powerful synergies in combination with checkpoint inhibitors to break therapeutic resistance and durably improve patient outcomes.